2016
DOI: 10.3746/pnf.2016.21.1.24
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antioxidant Activity of Aged Ginseng (Panax ginseng)

Abstract: Fresh ginseng roots were aged in an oven at 80°C for 14 d. The in vitro and in vivo antioxidant activities of this aged ginseng, in comparison with those of the white and red ginsengs, were evaluated. In in vitro antioxidant assays, the ethanolic extracts from aged ginseng showed significantly higher free radical scavenging activity and reducing power than those of the white and red ginsengs. In in vivo antioxidant assays, mice were fed a high fat diet supplemented with white, red, or aged ginseng powders. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…In our research, we aimed to unravel the antioxidant and immune-stimulatory activities of three different ginseng extracts in rats and mice. Although ginseng is already reported for its antioxidant properties [13] , [33] , our results clearly revealed that RGE possess good antioxidative ( Figs 1 A–D, E&F) and immune-stimulating ( Fig. 2 , Fig.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…In our research, we aimed to unravel the antioxidant and immune-stimulatory activities of three different ginseng extracts in rats and mice. Although ginseng is already reported for its antioxidant properties [13] , [33] , our results clearly revealed that RGE possess good antioxidative ( Figs 1 A–D, E&F) and immune-stimulating ( Fig. 2 , Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Many previous studies have reported how the processing time of ginseng (one time to many times) can change the composition of single ginseng compounds called “ginsenosides” [13] , [38] , [39] , [40] , [41] . Some studies have reported that excessive heat treatment of ginseng denatures the ginsenosides present in it, whereas some studies have reported that extensive processing of ginseng makes some of the important ginsenosides more bioavailable to the body than ginseng boiled and dried once [42] , [43] , [44] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were lyophilized and ground into powder using a blender (Shinil, Cheonan, ROK). The lyophilized powder was extracted as described previously (Chung et al, 2016a). Briefly, the powder (0.5 g) was extracted with 50 mL 80% methanol by mixing at 220 rpm at room temperature overnight.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In addition, 112 saponins were reported from raw or processed ginseng, including hydrolysates, semisynthetic, and metabolites [ 4 ]. Ginsenosides are known to possess a lot of biological activities including regulatory effects on immunomodulation, protection functions in the central nervous and cardiovascular systems, anti-diabetic, anti-aging, anti-carcinogenic, anti-fatigue, anti-pyretic, anti-stress, boosting physical vitality, and promotion of DNA, RNA, and protein synthesis activities [ 5 , 6 , 7 , 8 , 9 ]. In addition, the biosynthesis of triterpenoid is an important factor of saponin diversity.…”
Section: Introductionmentioning
confidence: 99%